Fire protection for commercial facilities - Bromann, Mark. (Boca Raton, FL : CRC Press, 2011)
'This book presents systems and practices that can increase a facility's ability to avoid fires, limit the development and spread of fires, and effectively control fires. Comprehensive in scope, it focuses on the many subfields of fire protection engineering that comprise the role of facility manager. Introducing managers to the wide array of fire protection engineering applications encountered during typical facility operations, it provides a good command of fire protection and fire prevention basics'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Commercial buildings -- Fires and fire prevention